Recovery techniques for Hydroxynaphthoquinone Enantiomers of Alkanna tinctoria (L.) from Natural Deep Eutectic Solvents: A Comparative Analysis - Bossard, Elodie; Tsafantakis, Nikolaos; Aligiannis, Nektarios; Chinou, Ioanna; Fokialakis, Nikolas (Planta Medica, 2025)
A natural deep eutectic solvent (NaDES) composed of levulinic acid and glucose using a molar ratio of 5 : 1 (molHBA:molHBD) and 20% of water (w/w) (LeG_5_20) was found as a great alternative to the commonly used organic solvents for the extraction of hydroxynaphthoquinone enantiomers (HNQs) from Alkanna tinctoria (L.) Tausch roots. In the present work, a comparative investigation of recovery methods for HNQs, such as solid-phase extraction, macroporous resin, and water as an anti-solvent, was performed to face the main disadvantage of NaDES: the inability to be evaporated. The highest recovery of HNQs was recorded using the solid-phase extraction on a reversed-phase C8 cartridge with a total hydroxynaphthoquinone content (TNC) of 46.79 ± 0.952 mg/g of dry weight (DW). In addition, a great recovery of HNQs was also reported for the macroporous resin Amberlite XAD 4 with a TNC value of 37.21 ± 1.789 mg/g DW, while the precipitation of HNQs by using water as an anti-solvent (1 : 5, v/v) offered a TNC value of 28.68 ± 0.023 mg/g DW. The macroporous resin Amberlite XAD also showed a great potential for larger-scale applications. In fact, the developed scale-up process, involving Amberlite XAD 4, showed a great recovery efficiency for HNQs (34.126 ± 1.093 mg/g DW), an acceptable robustness (RSD < 15%), and the possibility of recycling LeG_5_20 with a recovery greater than 50%; therefore, it is an excellent green alternative extraction procedure for HNQs.
Keywords: natural deep eutectic solvent; recovery; recycling; Alkanna tinctorial; hydroxynaphthoquinone enantiomers